Arctic Ocean, landscape of the North Pole - Ellsworth, Lincoln, 1880-1951 (1926)
"No. 18 Amundsen-Ellsworth 1925 Exped. The North Pole!" Caption taken from Ellsworth, L., & National Americana Society. (1929). Air Pioneering in the Arctic: the Two Polar Flights of Roald Amundsen and Lincoln Ellsworth (pp. 57, No.18). New York: National Americana Society.